Seorang Laki Laki 69 Tahun dengan Stroke Iskemik di Rumah Sakit Cut Meutia Aceh Utara - Rizki Irawan; Herlina Herlina (Lembaga Pengembangan Kinerja Dosen, 2026)
According to the World Health Organization (WHO), stroke is a clinical manifestation of focal or global cerebral dysfunction that occurs rapidly and lasts more than 24 hours or ends in death without any other underlying disease other than vascular disease. Based on data from the 2018 Basic Health Research (Riskesdas), the prevalence of stroke increases with age, with the highest incidence in the age group 75 years and above (50.2%) and the lowest in the age group 15-24 years (0.6%). Based on gender, the prevalence of stroke in men (11%) is almost the same as in women (10.9%). Hypertension is a major modifiable risk factor for both ischemic and hemorrhagic strokes. Hypertension can trigger atherosclerosis, which can encourage Low Density Lipoprotein (LDL) cholesterol to more easily enter the intimal layer of the blood vessel lumen and reduce the elasticity of the blood vessels. Hypertension can increase the risk of stroke by two to four times. A reduction of 10 to 12 mmHg for systolic blood pressure and 5 to 6 mmHg for diastolic blood pressure can reduce the incidence of stroke by 38%.